Student-Teacher Relationships As a Protective Factor for School Adjustment during the Transition from Middle to High School - Longobardi, Claudio; Prino, Laura E.; Marengo, Davide; Settanni, Michele (Frontiers in Psychology, 2016)
A robust body of research has identified school transitions during adolescence, and in particular the transition from middle to high school, as one of the riskiest phases for school failure, being characterized by significant social, emotional and behavioral changes. This transition is critical even with respect to academic achievement. In fact, in the Italian context, the highest frequency of students dropping-out from school can be observed in the 9th and 10th grades, partly as a consequence of a non-optimal adjustment to the new school-context. The impact of students’ relationships with their teachers may be particularly salient at critical developmental periods. Indeed, teacher-student relationships have been widely recognized as a form of protection to reduce the effect of risk factors in school adjustment and, in case of negative relationship quality, also a factor that increases the risk of maladjustment. Positive and affective student-teacher relationships may serve an important role for students’ adaptation to the school environment, favoring both achievement and adaptive behaviors. The aim of this study is to investigate the effects of the quality of teacher-student relationships, as perceived by pupils, on academic achievement and problem and prosocial behavior during the relevant school transition. The sample consists of 122 students (female = 55%). We employed a self-report questionnaire to collect information about: demographic characteristics, quality of relationship with teachers, problematic and prosocial behavior and academic achievement. Students filled in the questionnaires twice: during the 8th grade and 1 year later during their first year of high school (9th grade). Regression analyses indicated that both average and varying levels of closeness with teachers significantly predict changes in academic achievement: A perceived increase in closeness in 9th grade, as well as a higher mean closeness level, was associated with an increase in achievement. In turn, an increase in the level of perceived conflict with teachers significantly predicted an increase in conduct problems and hyperactivity/inattention symptoms. This study supports the significance of student-teacher relationships as a protective factor during the school transition to high-school. These findings indicate the importance of relationship quality in preventing risk of students’ school failure.